Family Based Education in Educating Youth Character - Harahap, Muhammad Yunan (Al-Fikru: Jurnal Ilmiah, 2022)
Implementation of strengthening family based character education is not an easy thing for parents to do. This is because, after the Covid-19 pandemic, many young people were poisoned by the flow of digitalization so they have bad characteristics, such as being addicted to online games. It is undeniable that currently almost all young people have gadgets and many of them use them incorrectly they affect behavior change. This study aims to find out how parents implement character education for the younger generation and the supporting and inhibiting factors in Lau Gumba Village, Karo Regency. The method used in this research is the descriptive qualitative method. The results of the study show that the implementation of family-based character education is manifested in the form of the attitude of parents who exemplify the spirit of work and responsibility, then instill humility and exemplary behavior in worship. Character education has supporting factors, namely the enthusiasm and strong motivation of parents in educating their children. While the inhibiting factor is the lack of understanding of the concept of character education in the family.